Strongly almost (?, ?, q)-summable sequences - Isik, Mahmut (Walter de Gruyter Gmbh, 2011)
The purpose of this paper is to introduce the spaces of sequences that are strongly almost (omega, lambda, q)-summable with respect to a modulus function. We give some relations related to these sequence spaces. It is also shown that if a sequence is strongly (omega, lambda, q)-summable with respect to a modulus function, then it is S(lambda (q) )-statistically convergent. (C) 2011 Mathematical Institute Slovak Academy of Sciences
Keywords: (omega, lambda, q)-summability; statistical convergence; modulus function